Analysis of Factors Affecting Employee Performance at PT Kurnia Agro Kemika Using the SMART PLS 3.0 Method - Agil Satriyo Adji; Sumiati Sumiati (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the influence of leadership on employee performance at PT. Kurnia Agro Kemika, both directly and through organizational culture. Specifically, this research examines (1) the effect of leadership on employee performance, (2) the effect of leadership on organizational culture, (3) the effect of organizational culture on employee performance, and (4) the role of organizational culture in mediating the relationship between leadership and employee performance.The method used in this study is Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach, utilizing SmartPLS 3.0 software. The analysis results indicate that leadership has a significant influence on organizational culture, organizational culture significantly affects employee performance, and leadership significantly impacts employee performance through organizational culture as a mediating variable.